Bamboo fiber reinforced polypropylene composites for transportation applications - Wasti, Sanjita; Kore, Surbhi; Yeole, Pritesh; Tekinalp, Halil; Ozcan, Soydan; Vaidya, Uday (Frontiers in Materials, 2022)
The Apitong wood species has long been the most popular choice for transportation, such as in trailer decking and shipping container floors. However, Apitong is depleting due to its excessive usage. Bamboo fiber provides as an alternative due to its low density (608-780 kg/m3) and lightweight attributes. This study explores (a) development and properties of bamboo-thermoplastic composites with different fiber content, and (b) application of bamboo composite in trailer decking (a transportation application) as an alternative to Apitong. Extrusion-compression and compression molding was used as processing approaches for the bamboo-thermoplastic composites. The basic panels were tested for flexural loading and nail pull out to evaluate the feasibility as a viable trailer decking material. The flexural strength and modulus of bamboo composite were found to be 17% and 98% higher than Apitong, respectively. The density of the bamboo-thermoplastic was 670kg/m3 compared to Apitong (737kg/m3), hence 10% lighter. The nail pull-out strength was comparable between the two. The work progressed to producing prototype trailer decking members via extrusion-compression and compression molding. The bamboo-composite decking was evaluated on a trailer test bed and exhibited excellent surface wear response, minimal internal damage and withstood 400 fatigue cycles with onset of failure only at the supports, which the span did not exhibit damage.